Sistem Pendukung Keputusan Penentuan Produk Terbaik Menggunakan Weighted Product Method - Vederico Pitsalitz Sabandar; Ridlan ahmad (Jurnal Ilmiah Computer Science, 2023)
The Weighted Product (WP) method is one of the methods in multi-criteria decision making used to evaluate alternatives based on predetermined criteria. This study aims to apply the WP method in determining the best products so as to help companies in marketing their products based on the results of the best product recommendations owned by the company. This study aims to apply the WP method in determining the best products so as to help companies in marketing their products based on the results of the best product recommendations owned by the company. The final result of the accumulated calculation of 4 customer assessments was obtained for rank 1 with a value of 0.904 obtained by Product E, rank 2 with a value of 0.83 obtained by Product A, rank 3 with a value of 0.794 obtained by Product D, rank 4 with a value of 0.771 obtained by Product C, and rank 5 with a value of 0.702 obtained by Product B.